2011
DOI: 10.1021/ac200501w
|View full text |Cite
|
Sign up to set email alerts
|

Direct Spectrophotometric Assay of Laccase Using Diazo Derivatives of Guaiacol

Abstract: The effects of 12 common metal ionic compounds on the laccase catalytic activity in reactions using guaiacol as the substrate was determined using spectrophotometry. Furthermore, the influence of several metal ionic compounds on the generation of reactive oxygen species (ROS) by oxidation of lignin in jute fiber under laccase catalysis was studied by electron paramagnetic resonance (EPR) spectroscopy using N-tert-butyl-alpha-phenylnitrone (PBN) as the spin-trapping agent. Common metal cations, such as K + , Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Previous studies showed that molecules carrying substituents at ortho M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 position to the binding terminal were poor inhibitors [10,20]. We also showed that guaiacols are not oxidized by MT, assumingly due to the spatial hindrance created by the methoxy group [31]. PA and CA have both benzene ring and CAFG in their structures, but neither serves as a substrate for MT.…”
Section: Introductionsupporting
confidence: 47%
“…Previous studies showed that molecules carrying substituents at ortho M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 position to the binding terminal were poor inhibitors [10,20]. We also showed that guaiacols are not oxidized by MT, assumingly due to the spatial hindrance created by the methoxy group [31]. PA and CA have both benzene ring and CAFG in their structures, but neither serves as a substrate for MT.…”
Section: Introductionsupporting
confidence: 47%
“…To date, the kinetics of laccase with guaiacol as a substrate have been studied by measuring the increase in absorbance at a wavelength of 470 nm, at which the oxidized form of the substrate shows the maximum absorption (Moshtaghioun et al, 2011;Manole et al, 2008). Considering that TTI monitoring is designed to provide a history of time-temperature along the food distribution chain for perishable products such as vegetables, meats, and dairy products, the color change should be easily measurable so that the amount of temperature abuse the product has been subjected to can be easily determined.…”
Section: Colorimetry Of Laccase Based Tti Prototypementioning
confidence: 99%
“…In some cases, laccases enhance the color formation by reaction with syringaldazine, hydroquinone, vanillic acid, tannic acid (Manole et al, 2008) and Diazo derivatives of guaiacol (Moshtaghioun et al, 2011). In the food industry, laccase is also used to modify, enhance, or change colors for foods and beverages to indicate safety (Minussi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since the structural skeleton of the examined substrates were the same and the enzymatic reactions were monitored directly through the consumption of the substrates, from the decrease in the substrate optical density at its λ max and not the formation of products, the changes in the kinetics could be solely ascribed to the effect of the substituents. Results of this study clearly showed the instant rates of the reactions (ÀdA/min) had the trend of -OCH 3 > -CH 3 % -H > -SO 2 NH 2 > -Cl, while the V max(s) of these substrates were in the same range (Moshtaghioun et al 2011). This result could be explained based on the radical nature of laccase reaction as the electron demand of organic radicals varies dramatically with the structure and induction effect of a substituent.…”
Section: Electronic Effect and Activitymentioning
confidence: 68%
“…To examine the electronic effect of a substituent, Moshtaghioun et al (2011) studied oxidation of some synthetic diazo derivatives of guaiacol (S1, Fig. 2) by the extracellular Neurospora crassa laccase.…”
Section: Electronic Effect and Activitymentioning
confidence: 99%